Production, removal and fate of steroid estrogens under the background of total sewage interception in the Erhai Lake Basin, China. Issue 1 (1st January 2020) - Shen, Jian; Li, Xueying; Wang, Xinze; Feng, Jimeng; Jiang, Shiyi; Zhang, Zhiping; Xu, Qian
ABSTRACT: The Erhai Lake basin dominated by agricultural production had a total sewage interception system and was selected as the study area. Survey data showed the total steroid estrogens (SEs) production was 55.97 kg/year (EEQ-E2β) in the whole basin and the main source of SEs was swine breeding (57%). The results indicated that unsatisfactory removal effect of SEs could be related to insufficient influent carbon sources as a result of the total sewage collection. The observed average concentrations of E1, E2α, E2β, E3 and EE2 in rivers/ditches were 25.9 ng/L, 43.5 ng/L, 14.4 ng/L, 49.4 ng/L and 24.5 ng/L, and SEs in ditches were significantly higher than that in rivers, proving the influence of the irrigation tailwater. Above, the annual SEs contribution for Erhai Lake was estimated, and the correlation coefficient of SEs and water quality of inflow rivers/ditches indicated that SEs had a certain correlation with nitrogen.